A nano-hybrid polymer, a preparation method and application thereof

CN117447660BActive Publication Date: 2026-10-30ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310214531.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2026-10-30
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

[0005]针对现有技术聚合物电解质存在离子电导率较低,界面稳定性差等问题,本发明的第一个目的是在于提供一种纳米杂化聚合物的制备方法

Benefits of technology

[0027](1)本发明的纳米杂化聚合物结晶度低,性能稳定,能够有效提高金属离子的传输速率,其含有大量醚氧原子,可与金属离子配位,所包含的表面改性二氧化硅表面具有大量的羟基基团,能够充当路易斯酸性位点吸附金属盐中的阴离子,从而提高金属离子迁移数;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117447660B_ABST
    Figure CN117447660B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nano hybrid polymer and its preparation method and application.The nano hybrid polymer is to 3-(trimethoxysilyl) propyl acrylate and nano silicon dioxide and water are mixed to carry out hydrolysis-grafting reaction, surface modified nano silicon dioxide is obtained;The surface modified nano silicon dioxide is mixed with methyl methacrylate polyethylene glycol methyl ether ester monomer solution and initiator to carry out free radical polymerization reaction, namely obtains.The ion conductivity of the nano hybrid polymer is high, and the thermal stability and mechanical performance are good, when it is used to prepare sodium ion battery electrolyte material, the transmission rate of sodium ion can be improved, and the ion conductivity of electrolyte is greatly improved.The preparation method is simple, and the cost is low, and it is suitable for industrial scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrolyte polymer material, specifically a nano-hybrid polymer, and also to its preparation method and application, belonging to the field of solid electrolyte material preparation technology. Background Technology

[0002] As the most widely used energy storage device, secondary batteries are ubiquitous in our lives. However, commercially available secondary lithium batteries mostly use liquid organic electrolytes. Because organic electrolytes contain toxic, low-flammability organic solvents, lithium / sodium secondary batteries are prone to catching fire or exploding under conditions of overcharging, short circuits, overheating, and severe impacts, posing a significant safety hazard.

[0003] Compared to liquid organic electrolytes, solid polymer electrolytes offer advantages such as lighter weight, better viscoelasticity, and easier film formation. They also allow batteries to be manufactured in various shapes to fully utilize available space, resulting in advantages such as ease of processing, impact resistance, and low cost. However, these polymer electrolytes also suffer from low conductivity and poor interfacial stability. Previous studies have shown that adding various composite additives such as inorganic particles, carbon nanotubes, and molecular sieves to polymer electrolytes can improve their morphology, thermal stability, mechanical properties, and electrochemical performance. However, the problem of particle aggregation limits further improvements in ionic conductivity.

[0004] Therefore, it is of great significance to develop a solid polymer electrolyte with high conductivity and stable performance. Summary of the Invention

[0005] To address the problems of low ionic conductivity and poor interfacial stability in existing polymer electrolytes, the first objective of this invention is to provide a method for preparing nano-hybrid polymers. This method is simple, operates under mild conditions, is low-cost, and suitable for large-scale industrial production.

[0006] A second objective of this invention is to provide a nano-hybrid polymer. This polymer exhibits low crystallinity, high thermal stability, and good mechanical properties, and when used in the preparation of electrolyte materials, it can improve ionic conductivity.

[0007] A third objective of this invention is to provide an application of the nano-hybrid polymer. The solid electrolyte prepared using this nano-hybrid polymer exhibits high ionic conductivity at room temperature.

[0008] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing a nano-hybrid polymer. The method involves mixing propyl 3-(trimethoxysilyl)acrylate, nano-silica, and water to carry out a hydrolysis-grafting reaction to obtain surface-modified nano-silica; and then mixing the surface-modified nano-silica with a polyethylene glycol methyl ether methacrylate monomer solution and an initiator to carry out a free radical polymerization reaction to obtain the final product.

[0009] In this invention, the molecular chains of the nano-hybrid polymer contain a large number of ether oxygen atoms, which can effectively coordinate metal ions (such as sodium ions). This invention uses 3-(trimethoxysilyl)acrylate to chemically modify the surface of nano-silica, enabling the silica to undergo free radical polymerization via the C=C double bonds of 3-(trimethoxysilyl)acrylate and the C=C double bonds of polyethylene glycol methyl ether methacrylate, uniformly introducing silica into the polymer matrix. The modified nano-silica reduces the crystallinity of the polymer matrix, thereby increasing the metal ion transport rate. Furthermore, because the modified nano-silica surface contains a large number of hydroxyl groups, these groups can act as Lewis acidic sites to adsorb anions from metal salts, thereby increasing the metal ion transport number.

[0010] As a preferred option, the molar ratio of propyl 3-(trimethoxysilyl)acrylate to nano-silica is 1~3:1.

[0011] During the chemical modification of nano-silica, if the molar ratio of propyl 3-(trimethoxysilyl)acrylate to nano-silica is too low, the propyl 3-(trimethoxysilyl)acrylate cannot be effectively and uniformly branched onto the surface of the nano-silica. However, if the molar ratio of propyl 3-(trimethoxysilyl)acrylate to nano-silica is too high, excess propyl 3-(trimethoxysilyl)acrylate will form a cross-linked structure on the surface of the nano-silica, affecting its subsequent processing.

[0012] As a preferred embodiment, the particle size of the nano-silica is 15~20 nm.

[0013] As a preferred embodiment, during the hydrolysis-grafting reaction, the pH of the mixed solution system is controlled at 3-4, the reaction temperature at 70-80℃, and the reaction time at 5-7h.

[0014] During the chemical modification of nano-silica, the siloxane groups in propyl 3-(trimethoxysilyl)acrylate can hydrolyze under acidic conditions and then react rapidly with the hydroxyl groups on the surface of nano-silica. Therefore, controlling the pH of the mixed solution system within a suitable range is beneficial to improving the reaction efficiency between propyl 3-(trimethoxysilyl)acrylate and nano-silica. Furthermore, controlling the temperature and time during the reaction process within a suitable range can yield modified silica with excellent performance. Excessively high reaction temperatures will damage the structure of the propyl 3-(trimethoxysilyl)acrylate monomer to some extent, while excessively low reaction temperatures will prevent the siloxane groups in propyl acrylate from being completely hydrolyzed. Simultaneously, during the hydrolysis process, excessively long times may cause modified nano-silica clusters, while excessively short times will not completely modify the silica.

[0015] As a preferred embodiment, the mass ratio of the surface-modified nano-silica to polyethylene glycol methyl ether methacrylate is 0.01~0.09:1.

[0016] As a preferred embodiment, the initiator is azobisisobutyronitrile (AIBN).

[0017] As a preferred embodiment, the amount of the initiator is 0.5 to 1% of the mass of polyethylene glycol methyl ether methacrylate monomer.

[0018] As a preferred embodiment, the conditions for the free radical polymerization reaction are: a temperature of 60-80°C and a time of 6-8 hours. The free radical polymerization reaction is carried out in a protective atmosphere, which is an inert gas.

[0019] In the polymer synthesis process, modified silica can undergo free radical polymerization via the C=C double bonds of propyl 3-(trimethoxysilyl)acrylate and polyethylene glycol methyl ether methacrylate. When the temperature is too low, the C=C double bonds cannot effectively undergo free radical polymerization, while when the temperature is too high, the chemical structure of the monomer will be damaged to some extent. Simultaneously, the reaction time also has a significant impact on polymer synthesis; too short a time results in incomplete reaction, while too long a time can cause cross-linking of the polymer. Therefore, rationally controlling the synthesis time and temperature is beneficial for obtaining a more ideal polymer structure.

[0020] This invention also provides a nano-hybrid polymer prepared by the above method. Because nano-silica is uniformly introduced into the matrix, the polymer exhibits low crystallinity and good thermal stability.

[0021] As a preferred embodiment, the content of surface-modified nano-silica in the nano-hybrid polymer is 1wt%-9wt%.

[0022] This invention also provides an application of a nano-hybrid polymer for preparing electrolyte materials for sodium-ion batteries. The molecular chain of this nano-hybrid polymer contains a large number of ether oxygen atoms, which can effectively coordinate with sodium ions. Through the continuous breaking / forming of sodium-oxygen bonds, sodium ion transport in the electrolyte occurs via intra- or inter-chain loops, which is beneficial for improving sodium ion transport efficiency.

[0023] As a preferred embodiment, the preparation process of the sodium-ion battery electrolyte material is as follows: the nano-hybrid polymer is mixed with sodium salt and solvent and then poured into a mold, and the solvent is evaporated to obtain the electrolyte.

[0024] As a preferred embodiment, the sodium salt is sodium perchlorate.

[0025] As a preferred embodiment, the molar ratio of sodium ions in the sodium salt to CH2CH2O polymerization units in the nano-hybrid polymer is 1:15~20, more preferably 1:20.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The nano-hybrid polymer of the present invention has low crystallinity and stable performance, which can effectively improve the transport rate of metal ions. It contains a large number of ether oxygen atoms, which can coordinate with metal ions. The surface-modified silica contained therein has a large number of hydroxyl groups, which can act as Lewis acid sites to adsorb anions in metal salts, thereby increasing the metal ion transport number.

[0028] (2) The sodium-ion battery electrolyte prepared by this nano-hybrid polymer has a high ionic conductivity at room temperature, which solves the problems of side reactions and concentration polarization of anions in traditional sodium-ion battery liquid electrolytes, and improves the coulombic efficiency and cycle life of the battery.

[0029] (3) The preparation method of polymer materials is simple, the raw materials are readily available, the cost is low, and it is suitable for industrial-scale production. Attached Figure Description

[0030] Figure 1 Infrared spectra of polyethylene glycol methyl ether methacrylate monomer (PEGMEM), surface-modified nano silica (γ-PTA-g-SiO2), and the nano-hybrid polymer (PEGMEN@nano-SiO2) prepared in Example 3.

[0031] Figure 2 The graph shows a comparison of the conductivity of the solid electrolytes prepared in Examples 1-5 at different temperatures.

[0032] Figure 3The graph shows a comparison of the conductivity of the solid electrolyte prepared in Example 3 with that prepared in Comparative Examples 1 and 2 at different temperatures. Detailed Implementation

[0033] The following examples are intended to further illustrate the present invention, rather than to limit the scope of the claims.

[0034] Conductivity measurements were performed using an SP-200 electrochemical workstation. The prepared nano-hybrid polymer electrolyte was assembled into an SS / SS (SS, stainless steel electrode) battery. The corresponding formula is:

[0035]

[0036] In the formula, denoted as ionic conductivity, L as electrolyte thickness, S as contact area between electrolyte and stainless steel electrode sheet, and R as electrolyte impedance.

[0037] Example 1

[0038] The first nano-hybrid polymer and electrolyte were prepared according to the following steps.

[0039] Step (1): Dissolve 2.3432 g of propyl 3-(trimethoxysilyl)acrylate and 0.3 g of nano-silica in 100 ml of deionized water, and disperse by ultrasonication for 30 min to obtain a mixed solution. Adjust the pH of the mixed solution to 3-4 with formic acid, and then stir at 75 °C for 5 h under argon atmosphere.

[0040] Step (2): After the reaction is complete, the precipitate is collected by centrifugation. The obtained solid is washed three times with deionized water and then dried in a vacuum oven at 50°C for 24 hours. The sample is named γ-PTA-g-SiO2.

[0041] In step (3), under argon atmosphere protection, 2g of PEGMEM, 0.02g of γ-PTA-g-SiO2 and 0.0101g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture PEGMEN@nano-SiO2 was obtained, in which the mass ratio of PEGMEM to γ-PTA-g-SiO2 was 100:1.

[0042] Step (4): Dissolve the mixed product obtained in step (3) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0043] In step (5), 1.3125 g of PEGMEN@nano-SiO2 and 0.1590 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE, denoted as NHPE1. At room temperature, the ionic conductivity was 2.95 × 10⁻⁶. -5 S / cm.

[0044] Example 2

[0045] The second nano-hybrid polymer and electrolyte were prepared according to the following steps.

[0046] Step (1): Dissolve 2.3432 g of propyl 3-(trimethoxysilyl)acrylate and 0.3 g of nano-silica in 100 ml of deionized water, and disperse by ultrasonication for 30 min to obtain a mixed solution. Adjust the pH of the mixed solution to 3-4 with formic acid, and then stir at 75 °C for 5 h under argon atmosphere.

[0047] Step (2): After the reaction is complete, the precipitate is collected by centrifugation. The obtained solid is washed three times with deionized water and then dried in a vacuum oven at 50°C for 24 hours. The sample is named γ-PTA-g-SiO2.

[0048] In step (3), under argon atmosphere protection, 2g of PEGMEM, 0.06g of γ-PTA-g-SiO2 and 0.0103g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture PEGMEN@nano-SiO2 was obtained, in which the mass ratio of PEGMEM to γ-PTA-g-SiO2 was 100:3.

[0049] Step (4): Dissolve the mixed product obtained in step (3) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0050] In step (5), 1.3625 g of PEGMEN@nano-SiO2 and 0.1651 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE, denoted as NHPE3. At room temperature, the ionic conductivity was 3.17 × 10⁻⁶. -5 S / cm.

[0051] Example 3

[0052] The third nano-hybrid polymer and electrolyte were prepared according to the following steps.

[0053] Step (1): Dissolve 2.3432 g of propyl 3-(trimethoxysilyl)acrylate and 0.3 g of nano-silica in 100 ml of deionized water, and disperse by ultrasonication for 30 min to obtain a mixed solution. Adjust the pH of the mixed solution to 3-4 with formic acid, and then stir at 75 °C for 5 h under argon atmosphere.

[0054] Step (2): After the reaction is complete, the precipitate is collected by centrifugation. The obtained solid is washed three times with deionized water and then dried in a vacuum oven at 50°C for 24 hours. The sample is named γ-PTA-g-SiO2.

[0055] In step (3), under argon atmosphere protection, 2g of PEGMEM, 0.1g of γ-PTA-g-SiO2 and 0.0105g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture PEGMEN@nano-SiO2 was obtained, in which the mass ratio of PEGMEM to γ-PTA-g-SiO2 was 20:1.

[0056] Step (4): Dissolve the mixed product obtained in step (3) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0057] In step (5), 1.4123 g of PEGMEN@nano-SiO2 and 0.1711 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE, denoted as NHPE5. At room temperature, the ionic conductivity was 3.27 × 10⁻⁶. -5 S / cm.

[0058] In this embodiment, the PEGMEN@nano-SiO2 polymer has a γ-PTA-g-SiO2 content of 5%, and the polymer infrared spectrum is shown below. Figure 1 As shown. From Figure 1 As can be seen from the data, the characteristic absorption peaks of C=C vibration in the original PEGMEM and γ-PTA-g-SiO2 monomers disappeared after polymerization, indicating that the two monomers had polymerized.

[0059] Example 4

[0060] The fourth nano-hybrid polymer and electrolyte were prepared according to the following steps.

[0061] Step (1): Dissolve 2.3432 g of propyl 3-(trimethoxysilyl)acrylate and 0.3 g of nano-silica in 100 ml of deionized water, and disperse by ultrasonication for 30 min to obtain a mixed solution. Adjust the pH of the mixed solution to 3-4 with formic acid, and then stir at 75 °C for 5 h under argon atmosphere.

[0062] Step (2): After the reaction is complete, the precipitate is collected by centrifugation. The obtained solid is washed three times with deionized water and then dried in a vacuum oven at 50°C for 24 hours. The sample is named γ-PTA-g-SiO2.

[0063] In step (3), under argon atmosphere protection, 2g of PEGMEM, 0.14g of γ-PTA-g-SiO2 and 0.0107g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture PEGMEN@nano-SiO2 was obtained, in which the mass ratio of PEGMEM to γ-PTA-g-SiO2 was 100:7.

[0064] Step (4): Dissolve the mixed product obtained in step (3) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0065] In step (5), 1.4536 g of PEGMEN@nano-SiO2 and 0.1761 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE, denoted as NHPE7. At room temperature, the ionic conductivity was 3.0 × 10⁻⁶. -5 S / cm.

[0066] Example 5

[0067] The fifth nano-hybrid polymer and electrolyte were prepared according to the following steps.

[0068] Step (1): Dissolve 2.3432 g of propyl 3-(trimethoxysilyl)acrylate and 0.3 g of nano-silica in 100 ml of deionized water, and disperse by ultrasonication for 30 min to obtain a mixed solution. Adjust the pH of the mixed solution to 3-4 with formic acid, and then stir at 75 °C for 5 h under argon atmosphere.

[0069] Step (2): After the reaction is complete, the precipitate is collected by centrifugation. The obtained solid is washed three times with deionized water and then dried in a vacuum oven at 50°C for 24 hours. The sample is named γ-PTA-g-SiO2.

[0070] In step (3), under argon atmosphere protection, 2g of PEGMEM, 0.18g of γ-PTA-g-SiO2 and 0.0109g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture PEGMEN@nano-SiO2 was obtained, in which the mass ratio of PEGMEM to γ-PTA-g-SiO2 was 100:9.

[0071] Step (4): Dissolve the mixed product obtained in step (3) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0072] In step (5), 1.5135 g of PEGMEN@nano-SiO2 and 0.1834 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE, denoted as NHPE9. At room temperature, the ionic conductivity was 2.53 × 10⁻⁶. -5 S / cm.

[0073] like Figure 2 As shown, the conductivity of the solid electrolytes prepared in Examples 1-5 and Comparative Example 1 was tested at different temperatures. Figure 2 As can be seen, the conductivity of the composite electrolyte membrane SiO2-grafted NHPE increases with increasing temperature. The highest conductivity is achieved when the mass ratio of PEGMEM:γ-PTA-g-SiO2 is 20:1, reaching 3.27 × 10⁻⁶ at 25℃. -5 S / cm.

[0074] Example 6

[0075] The nano-hybrid polymer was prepared using the method of Example 3, except that the amount of propyl 3-(trimethoxysilyl)acrylate was 0.5858 g.

[0076] 1.4975 g of PEGMEN@nano-SiO2 prepared under the given conditions and 0.1814 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and vacuum dried to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE. At room temperature, the ionic conductivity was 1.83 × 10⁻⁶. -5 S / cm.

[0077] Example 7

[0078] The nano-hybrid polymer was prepared using the method of Example 3, except that the amount of propyl 3-(trimethoxysilyl)acrylate was 5.8580 g.

[0079] 1.5236 g of PEGMEN@nano-SiO2 prepared under the given conditions and 0.1845 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and vacuum dried to obtain the nano-hybrid polymer electrolyte SiO2-grafted NHPE. At room temperature, the ionic conductivity was 2.17 × 10⁻⁶. -5 S / cm.

[0080] Comparative Example 1

[0081] The polymer electrolyte is prepared by a simple free radical polymerization reaction of pure PEGMEM matrix, specifically following these steps:

[0082] In step (1), under argon atmosphere, 2g of PEGMEM and 0.01g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a 70℃ water bath for 8 hours with magnetic stirring. After the simple free radical polymerization was complete, a viscous mixture was obtained. This mixture was dissolved in ethyl acetate and then precipitated with petroleum ether. After washing three times, a white transparent polymer was obtained, which was then dried in a vacuum oven at 60℃ for 24 hours.

[0083] In step (2), 1.4236 g of PEGMEM polymer and 0.1743 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and dried under vacuum to obtain pure PEGMEM polymer electrolyte, which can be designated as SPE. At room temperature, the ionic conductivity was 1.65 × 10⁻⁶. -5 S / cm.

[0084] Comparative Example 2

[0085] Based on Comparative Example 1, nano-silica was added to PEGMEM via a simple physical blending method. The composite polymer electrolyte was prepared according to the following steps:

[0086] In step (1), under argon atmosphere protection, 2g of PEGMEM, 0.1g of SiO2 and 0.01g of AIBN were added to a three-necked flask containing 20mL of ethyl acetate. The mixture was reacted in a water bath at 70℃ for 8h with magnetic stirring. After the simple free radical polymerization reaction was completed, a viscous mixture of PEGMEN / SiO2 was obtained. The mass ratio of PEGMEM to SiO2 was 20:1.

[0087] Step (2) Dissolve the mixed product obtained in step (1) in ethyl acetate and then precipitate it with petroleum ether. After washing three times, a white transparent polymer is obtained and then placed in a vacuum oven at 60°C for 24 hours.

[0088] In step (3), 1.4486 g of PEGMEN / SiO2 and 0.1689 g of sodium perchlorate were dissolved in 4 ml of tetrahydrofuran solution. After stirring at room temperature for 12 h, the solution was poured into a polytetrafluoroethylene mold and vacuum dried to obtain the nanocomposite polymer electrolyte SiO2-blended NHPE. At room temperature, the ionic conductivity was 1.74 × 10⁻⁶. -5 S / cm.

[0089] like Figure 3 As shown, the conductivity of the solid electrolytes obtained in Example 3 and Comparative Examples 1-2 was tested at different temperatures. Figure 3 As can be seen, the conductivity of all three increases with increasing temperature, with the electrolyte membrane chemically grafted with SiO2 exhibiting the highest conductivity, reaching 3.27 × 10⁻⁶ at 25 °C. -5 S / cm.

Claims

1. A method for preparing a nano-hybrid polymer, characterized in that: 3-(trimethoxysilyl)propyl acrylate, nano-silica, and water are mixed and subjected to a hydrolysis-grafting reaction to obtain surface-modified nano-silica; the surface-modified nano-silica is then mixed with a polyethylene glycol methyl ether methacrylate monomer solution and an initiator for a free radical polymerization reaction to obtain the final product.

2. The method for preparing a nano-hybrid polymer according to claim 1, characterized in that: The molar ratio of 3-(trimethoxysilyl)acrylate to nano-silica is 1 to 3:

1.

3. A method for preparing a nano-hybrid polymer according to claim 1 or 2, characterized in that: During the hydrolysis-grafting reaction, the pH of the mixed solution system is controlled at 3-4, the reaction temperature at 70-80℃, and the reaction time at 5-7h.

4. The method for preparing a nano-hybrid polymer according to claim 1, characterized in that: The mass ratio of the surface-modified nano-silica to polyethylene glycol methyl ether methacrylate is 0.01 to 0.09:1; The initiator is azobisisobutyronitrile; The amount of the initiator is 0.5 to 1% of the mass of polyethylene glycol methyl ether methacrylate monomer.

5. A method for preparing a nano-hybrid polymer according to claim 1 or 4, characterized in that: The conditions for the free radical polymerization reaction are: temperature 60–80°C and time 6–8 h.

6. A nano-hybrid polymer, characterized in that: Prepared by the method described in any one of claims 1 to 5.

7. The application of the nano-hybrid polymer according to claim 6, characterized in that: Used to prepare electrolyte materials for sodium-ion batteries.

8. The application of the nano-hybrid polymer according to claim 7, characterized in that: The preparation process of the sodium-ion battery electrolyte material is as follows: the nano-hybrid polymer is mixed with sodium salt and solvent and then poured into a mold, and the solvent is evaporated to obtain the electrolyte.

9. The application of the nano-hybrid polymer according to claim 8, characterized in that: The sodium salt is sodium perchlorate; The molar ratio of sodium ions in the sodium salt to CH2CH2O polymer units in the nano-hybrid polymer is 1:15 to 20.